Intraventricular Hemorrhage: Risk Factors and Association With Patent Ductus Arteriosus Treatment in Extremely Preterm Neonates - Khanafer-Larocque, Ijab; Soraisham, Amuchou; Stritzke, Amelie; Al Awad, Essa; Thomas, Sumesh; Murthy, Prashanth; Kamaluddeen, Majeeda; Scott, James N.; Mohammad, Khorshid (Frontiers in Pediatrics, 2019)
Objectives To assess maternal and neonatal risk factors for intraventricular hemorrhage (IVH). To examine the association of patent ductus arteriosus (PDA) and its treatment with IVH and its severity. Study design Prospective cohort study of 495 neonates <29+0 weeks, admitted to a Level III Neonatal Intensive Care Unit (NICU) in Calgary, Canada, between 2013 and 2016, who had a head ultrasound in the first 7 days of life. A subset analysis included 258 neonates who had early cardiac imaging. The primary study outcome was severity of IVH. Tests used were two-sided and significance was defined as p-value <0.05. Results Of the 495 neonates, 121 (24.4%) had IVH of any grade and 48 (9.7%) had severe IVH. Identified risk factors are small birth gestation and weight, lack of antenatal corticosteroids, being outborn, vaginal delivery, maternal chorioamnionitis, respiratory distress syndrome, CO2 fluctuations, sedation, acidosis, inotropes or saline boluses use, and bicarbonate/THAM therapy. Medical treatment was received in 194 (39%) neonates. A PDA requiring treatment was associated with a higher risk of IVH. There was no significant difference in the incidence of IVH between neonates with early treatment of PDA compared to late, however early indomethacin treatment was associated with decreased severity of IVH. In the secondary analysis, 142 (55%) neonates had a hemodynamically significant PDA (Hs-PDA), and of those with severe IVH, 18 (55%) had a Hs-PDA; this is clinically but not statistically significant. Conclusions Identified risk factors should be the aim of IVH reduction bundles. Early indomethacin treatment decreases IVH severity.